2012
DOI: 10.4103/0974-620x.106094
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome and impact on quality of life after surgeries differ in children operated for unilateral and bilateral cataract (Pune study 2011)

Abstract: Background:We compared vision and quality of life (VQL) of children aged 5-15 years and operated for unilateral and bilateral cataract between 2008 and 2010 in western India.Materials and Methods:In this cohort study, ophthalmologists assessed vision, anterior and posterior segment of eyes with cataract. Children completed a functional vision questionnaire (LVP-FVQ). Follow up at 6 months after surgery included the best corrected visual acuity (BCVA), FVQ and eye assessment. The improvement of BCVA and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Prasad-Functional Vision Questionnaire can also serve as a valid measure of self-reported functional vision performance for visually impaired children. [15][16][17] However, these questionnaires were specifically designed for children with vision impairment but not for other eye conditions. Reduced quality of life (QOL) was found among children with different ophthalmic disorders using the PedsQL (Paediatric Quality of Life Inventory), [18][19][20] a generic questionnaire that systematically assesses the health-related QOL (HRQOL) of paediatric patients with chronic conditions, 21 but the PedsQL is reported to be less sensitive to the concerns of children with eye diseases compared with newer eye-specific questionnaires.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Prasad-Functional Vision Questionnaire can also serve as a valid measure of self-reported functional vision performance for visually impaired children. [15][16][17] However, these questionnaires were specifically designed for children with vision impairment but not for other eye conditions. Reduced quality of life (QOL) was found among children with different ophthalmic disorders using the PedsQL (Paediatric Quality of Life Inventory), [18][19][20] a generic questionnaire that systematically assesses the health-related QOL (HRQOL) of paediatric patients with chronic conditions, 21 but the PedsQL is reported to be less sensitive to the concerns of children with eye diseases compared with newer eye-specific questionnaires.…”
Section: Open Accessmentioning
confidence: 99%
“…Khadka et al developed the Cardiff Visual Ability Questionnaire for Children to assess self-reported visual ability in children and young people with visual impairment 14. The LV Prasad-Functional Vision Questionnaire can also serve as a valid measure of self-reported functional vision performance for visually impaired children 15–17. However, these questionnaires were specifically designed for children with vision impairment but not for other eye conditions.…”
Section: Introductionmentioning
confidence: 99%